2022
DOI: 10.1101/2022.09.15.22280012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viable Monkeypox virus in the environment of a patient room

Abstract: We conducted a prospective environmental surveillance study to investigate the air, surface, dust and water contamination of a room occupied by a patient infected with Monkeypox virus (MPXV) at various stages of his illness. The patient tested positive for MPXV from a throat swab and skin lesions. Environmental sampling was conducted in a negative pressure room with 12 unidirectional HEPA air changes per hour and daily cleaning of the surfaces. A total of 179 environmental samples were collected on days 7, 8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is currently thought that certain activities could cause the mpox virus to be suspended in the air 30 . Practices that could aerosolize virus particles, such as shaking bed linens or an aerosol‐generating procedure (such as intubation) 52 or such as opening of doors, 29 vacuum cleaning and transport of contaminated items for washing, 38 should be avoided; therefore, the need for healthcare professionals to wear the proper respiratory protection when conducting tasks that could cause infectious material to be suspended in polluted surroundings is essential 30 . Further studies are needed to evaluate the extent to which the presence of mpox virus DNA in the air could affect immunocompromised patients in healthcare facilities, and further epidemiological studies are crucial, especially in Africa.…”
Section: Type Sample Mpox Strain Used Referencesmentioning
confidence: 99%
“…It is currently thought that certain activities could cause the mpox virus to be suspended in the air 30 . Practices that could aerosolize virus particles, such as shaking bed linens or an aerosol‐generating procedure (such as intubation) 52 or such as opening of doors, 29 vacuum cleaning and transport of contaminated items for washing, 38 should be avoided; therefore, the need for healthcare professionals to wear the proper respiratory protection when conducting tasks that could cause infectious material to be suspended in polluted surroundings is essential 30 . Further studies are needed to evaluate the extent to which the presence of mpox virus DNA in the air could affect immunocompromised patients in healthcare facilities, and further epidemiological studies are crucial, especially in Africa.…”
Section: Type Sample Mpox Strain Used Referencesmentioning
confidence: 99%
“…2 In support of such findings, viable mpox virus has been detected on various surfaces in home and hospital settings of infected individuals (Table 1). [3][4][5][6][7][8] One quantitative study of viable mpox virus in a residential setting found the highest level on underwear. 3 Viable mpox has been detected on household surfaces for up to 15 days, but at low titers suggesting a lesser potential for transmission.…”
mentioning
confidence: 99%